If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(m+4)=2(-4-m+3)
We move all terms to the left:
5(m+4)-(2(-4-m+3))=0
We add all the numbers together, and all the variables
5(m+4)-(2(-1m-1))=0
We multiply parentheses
5m-(2(-1m-1))+20=0
We calculate terms in parentheses: -(2(-1m-1)), so:We get rid of parentheses
2(-1m-1)
We multiply parentheses
-2m-2
Back to the equation:
-(-2m-2)
5m+2m+2+20=0
We add all the numbers together, and all the variables
7m+22=0
We move all terms containing m to the left, all other terms to the right
7m=-22
m=-22/7
m=-3+1/7
| 2m-6+5-2m=4m+5-2 | | 2(6x-10)=0 | | -12-9m-14=-10m-20 | | 30x=-4+16x | | -8a=4-7a | | 3y+6=-30 | | 9/3=5/n | | 4x+42x=2(x+2) | | 5x+18=-2x+11 | | -3z-9=-4z | | 21x=26x | | –3x–8=–14. | | 2x+(2x-1)+(5x-2)=180 | | 5(n-8)=6(1-3n) | | 3+2x=15-5x | | 7(2x–30)=84 | | 27v-160-32v=-2 | | 7x+12=11x+6 | | 3(2x-4)-6x=-6x-12 | | 3x+9=15 | | 300x+5=240x+125 | | -6y+4=-8y | | -5x=(4/5x2) | | -18p=-19p+15 | | 2/x=-2 | | -2|2.2x-3.3=-6.6 | | 8+18h+3h=19h-2 | | 2(3x-4)=2(2x+1) | | -3g=15 | | 0.02x=325 | | -12r+10=-40r+10 | | 6+13x+29x+6=180 |